Increased of Spleen White Pulp Diameter Post Dbl2β-Pfemp1 Recombinant Protein Injection in Wistar Rats: Pre-Clinical Study for Malaria Vaccine Development - Erma Sulistyaningsih; Nindya Audatus Sa’diyah; Irawan Fajar Kusuma; Rosita Dewi; Sheilla Rachmania (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2024)
Malaria is a major infectious disease worldwide, and vaccination is essential for disease control. The Plasmodium falciparum Erythrocyte Membrane Protein-1 (PfEMP1) is a potential malaria vaccine candidate due to its involvement in pathogenesis. Injection of DBL2β-PfEMP1 recombinant protein in animal models induces IgG and CD4+ production and inhibits binding with host endothelial receptors. This study aimed to analyze the spleen immune response by measuring the white pulp diameter. The experimental study used Wistar rats (Rattus norvegicus) that were divided into four groups, a control group and three treatment groups, which were injected with 100, 150, and 200 μg of DBL2β-PfEMP1 protein. Injection was done thrice with three-week intervals (days 0, 21, and 42). On day 56, rats were euthanized, and spleens were prepared for histology examination. The white pulp diameter increased along with increasing the dose of protein. The ANOVA test showed a significant difference between groups (p=0.001). The posthoc Bonferroni test showed a significant difference between the control and the 150 and 200 μg groups and the 100 μg and 200 μg groups. In conclusion, the DBL2β-PfEMP1 recombinant protein injection increased the spleen white pulp diameter in Wistar rats, and the 200 μg dose resulted in the highest increase.